2019
DOI: 10.3390/sports7030059
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Recovery Following Resistance Exercise with Different Loading Magnitudes and Velocity Loss in the Set

Abstract: The aim of this study was to compare the time course of recovery following four different resistance exercise protocols in terms of loading magnitude (60% vs. 80% 1RM—one-repetition maximum) and velocity loss in the set (20% vs. 40%). Seventeen males performed four different protocols in full squat exercise, which were as follows: (1) 60% 1RM with a velocity loss of 20% (60-20), (2) 60% 1RM with a velocity loss of 40% (60-40), (3) 80% 1RM with a velocity loss of 20% (80-20), and (4) 80% 1RM with a velocity los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 27 publications
3
40
3
Order By: Relevance
“…This result is very relevant for those athletes who are required to attain high strength levels during the entire season, with competitions every weekend or even every 3‐4 days. It has been shown that RT protocols with large VL thresholds require longer recovery times (up to 48 hours post‐exercise), whereas low VL thresholds show faster rates of recovery 30,31 . Therefore, including RT protocols with lower VL thresholds during in‐season periods with congested calendars could produce significant strength adaptations while maximizing recovery, compared with higher VL thresholds that may be detrimental to muscle recovery.…”
Section: Discussionmentioning
confidence: 99%
“…This result is very relevant for those athletes who are required to attain high strength levels during the entire season, with competitions every weekend or even every 3‐4 days. It has been shown that RT protocols with large VL thresholds require longer recovery times (up to 48 hours post‐exercise), whereas low VL thresholds show faster rates of recovery 30,31 . Therefore, including RT protocols with lower VL thresholds during in‐season periods with congested calendars could produce significant strength adaptations while maximizing recovery, compared with higher VL thresholds that may be detrimental to muscle recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the great interest in new resistance training approaches such as VBT (Courel-Ibáñez et al, 2019;Pareja-Blanco et al, 2019;Pérez-Castilla et al, 2019a;Weakley et al, 2020a), there is limited scientific data measuring the real effort applied in each training session (by monitoring movement velocity). This study presented the novelty of assessing VL of a daily adjustment of training loads based on velocity, to match the relative programmed intensity (for the AL group) or using previously determined absolute loads corresponding to the programmed RI without modifying loads daily (for the NAL group) in two RT programs identical with regard to volume (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…when velocity of movement dropped to 70% of the peak attained. A recent similar study (Pareja-Blanco et al, 2019) compared four different protocols in terms of load (60 and 80%) and velocity loss (20 and 40%) in the squat exercise and measured the countermovement vertical jump, 20m sprint time and movement velocity against the load that elicited a 1 m·s-1 velocity, before and 10 s, 6 h, 24 h and 48 h later. Those authors observed that a larger exercise volume load, resulting from a greater velocity loss (by 40%) and the lower load of 60% of 1RM resulted not only in greater acute fatigue, but also in decreased vertical jump performance 6 and 24 h later.…”
Section: Discussionmentioning
confidence: 99%